Left in the Dark: Regimes of Affect and Political Passivity in Kazuo Ishiguro's the Remains of the Day - Oz, Ozge (Routledge Journals, Taylor & Francis Ltd, 2023)
In one of the latest commentaries on Kazuo Ishiguro's novel The Remains of the Day (1989), it is explained that the novel's protagonist Stevens is a true monster who has embraced antisemitism and fascism throughout his career and it is also underlined that although there is no question about Stevens's emotional repression horizontal ellipsis this trait has little to do with his racism and refusal to intervene morally in Darlington's household. The present paper aims to offer an alternative reading of the political agency and passivity of the novel's protagonist Stevens with the help of affect theory. This paper will read The Remains of the Day and its protagonist primarily by looking at their relationship with sense reception, motion, and emotion, and show that the apathy and affective restraint experienced by Stevens as an English butler underlies his political passivity. Such a reading will also enable the readers to perceive Ishiguro's work as a hopeful narrative affirming the power of affect in the matters of political emancipation and agency.